Exploring Aquaculture Fish Production: The Case of South Aceh District - Muti'ah Muti'ah; M. Shabri Abd Majid; Chenny Seftarita; Yahya Yahya (Department of Aquaculture, 2022)
This study empirically explores factors determining the production of fish aquaculture in the South Aceh District, Indonesia. The study selected 150 out 1,893 aquaculture fish farmers within 18 sub-districts in the regency as the study’s respondents using a multi-stage sampling technique. Primary data collected through questionnaires’ distribution were analyzed employing a multiple regression model. The research documented empirical evidence that fish pond area, number of fish farmers, and capital significantly and positively influenced the production of fish aquaculture in the South Aceh Regency. Meanwhile, the number of fish seeds had an insignificant impact on the production of fish aquaculture. These empirical results suggested that in improving aquaculture fish production, fish farmers have to possess an adequate amount of capital, pond area, and the number of workers. Soft loan assistance sourced either from the government or banking institutions, conversion of idle and abandoned lands into fish ponds, and various fisheries capacity building programs is among the strategic steps that require to be taken to extend aquaculture production.